PENGARUH CORPORATE GOVERNANCE TERHADAP PERINGKAT DAN YIELD OBLIGASI DI BEI - Sihotang Dikson Terry (Jurnal Riset Manajemen dan Bisnis, 2011)
The purpose of this study is to examine weather corporate governance impact on bond yield and rating. This study analyses sample 27 of bonds made of Indonesian Stock Exchangelisted finance firms over the period 2004-2008. Data is analysed by using multivariate logistic regression dan multivariate regression. Multivariate logistic regres-sion is used to analyse the effect of corporate governance impact on bond rating. Meanwhile, multivariateregres-sion is used to analyse the effect of corporate governance impact on bond yield. The analyses show two main findings. First, Independent board have negative impact on bond rating. How-ever, the coefficient of the variable result is not consistent with the prediction.  Second, institutional ownership have negative impact on bond yield.Keywords: Corporate Governance, Bond Rating, Bond Yield